KEPADATAN DAN KERAGAMAN SPORA FUNGI MIKORIZA ARBUSKULA PADA DAERAH PERAKARAN BEBERAPA TANAMAN PANGAN DI LAHAN PERTANIAN DESA SIDERA - Yusriadi Yusriadi; Yosep Soge Pata’dungan; Uswah Hasanah (Universitas Tadulako, 2018)
This study aimed to determine the density and diversity of spores of arboscularmycorrhizal fungi (AMF) inrhizosphereof five crops. The method used in this research was exploratory descriptive. The sites of soil samples taken were done purposively around the rizhospere of the plant selected. Soil analysis and spore observations were conducted in the Laboratory of Soil Science and in the Laboratory of Agronomy of Faculty of Agriculture of Tadulako University, respectively. Higher number of spores was found in the rhizosphere of soybean and only a few numbers in cassava rhizosphere. Low soil pH, P-total and C-organic tend to lower the number of spore living around the crop rhizosphere. The morphological characteristics of the spores found included sphere, ellipse, and oval, while the color comprised of brown, dark brown, transparent, yellow and brownish yellow. The size of the arbuscular spores ranged from 63 – 250 mm. Keywords: Arboscularmycorrhizal fungi, crops, and rhizosphere.